Dobrovolskyite, Na4Ca(SO4)3, a new fumarolic sulfate from the Great Tolbachik fissure eruption, Kamchatka Peninsula, Russia. (29th April 2021) - Shablinskii, Andrey P.; Filatov, Stanislav K.; Krivovichev, Sergey V.; Vergasova, Lidiya P.; Moskaleva, Svetlana V.; Avdontseva, Eugeniya Yu.; Knyazev, Alexander V.; Bubnova, Rimma S.
Abstract: Dobrovolskyite, Na4 Ca(SO4 )3, is a new sulfate mineral from the Great Tolbachik fissure eruption, Kamchatka peninsula, Russia. It occurs as aggregates of tabular crystals up to 1–2 mm in maximum dimension, with abundant gas inclusions. The empirical formula calculated on the basis of O = 12 is (Na3.90 K0.10 )Σ4 (Ca0.45 Mg0.16 Cu0.12 Na0.10 )Σ0.83 S3.08 O12 . The crystal structure of dobrovolskyite was determined using single-crystal X-ray diffraction data as: trigonal, R 3, a = 15.7223(2), c = 22.0160(5) Å, V = 4713.1(2) Å 3, Z = 18 and R 1 = 0.072. The Mohs' hardness is 3.5. The mineral is uniaxial (+), with ω = 1.489(2) and ɛ = 1.491(2) (λ = 589 nm). The seven strongest lines of the powder X-ray diffraction pattern [ d, Å ( I, %)( hkl )] are: 11.58(40)(101); 5.79(22)(202); 4.54(18)(030); 3.86(88)(033); 3.67(32)(006); 2.855(50)(306); and 2.682(100)(330). The mineral is named in honour of Prof. Dr. Vladimir Vitalievich Dolivo-Dobrovolsky (1927–2009), one of the leading Russian scientists in the field of petrology, crystal optics and crystal chemistry. The crystal structure of dobrovolskyite can be described as composed of three symmetrically independent rods running parallel to the c axis. The rods consist of six octahedral–tetrahedral [Na(SO4 )6 ] 11– or [Ca(SO4 )6 ] 10– clusters of central octahedra sharing common corners with six adjacent SO4 tetrahedra. Alternatively, the crystal structure of the mineral can be described as a 12-layer ABACABACABAC eutactic array of Na + and Ca 2+ cations, and vacancies with disordered (SO4 ) tetrahedra in interstices. Dobrovolskyite and similar minerals probably formed upon cooling of a high-temperature phase with disordered cation and anion arrangements.